SISTEM APLIKASI PENGAWASAN AKADEMIK PADA SMAN 1 KENDARI BERBASIS WEB - La Ane; Bambang Pramono; Statiswaty Statiswaty (Informatics Engineering Department of Halu Oleo University, 2016)
Supervision grades and student attendance is still carried out in general that the parents come to the school to check students' grades and attendance, which led the parents of students experiencing difficulties in conducting monitoring student grades and attendance. The purpose of this research is to design academic supervision applications that can help parents to supervise the learning outcomes siswa.Metode development system used in the design of this system is the Rational Unified Process (RUP). Analysis and design of systems using modeling usecase diagrams, activity diagrams and sequence diagram. The used software in building this application is PHP as the programming language and MySQL as the database server. This application features and value checking student attendance, grades and attendance inputting and printing of a book report cards. By Application Academic Supervision of this document or file that is now more organized, because it is already stored in the computer. Keywords— Website, PHP, MySQL, RUP, Academic Supervision.